2018
DOI: 10.4274/jtgga.2017.0047
|View full text |Cite
|
Sign up to set email alerts
|

Does progesterone have protective effects on ovarian ischemia-reperfusion injury?

Abstract: Objective:The aim of the present study was to evaluate the effects of progesterone (PG) against ovarian ischemia-reperfusion (I/R) injury through the evaluation of biochemical and histopathologic parameters.Material and Methods:Twenty-one female Wistar albino rats were divided into three groups. Group 1: Sham; group 2: I/R; group 3: I/R+PG (8 mg/kg). PG was administered intraperitoneally to the rats in group 3, 30 minutes before a detorsion operation. Ovarian I/R injury was evaluated in serum and tissue by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…11 Banu Güleç et al made the assumption that preoperative Progesterone (PG) treatment might exert protective effects on ovarian I/R injury through its anti-apoptotic and antioxidative properties; since serum and tissue TOS levels, histologic score including vascular congestion, hemorrhage, polymorphonuclear neutrophils, number of apoptotic cells and interstitial edema were significantly lower and tissue TAS levels were higher in treated group (p<0.001). 12 However, the PG pre-treatment decrease was not statistically significant. The present experiment shows that L attenuates the cytokine TNFα levels which is involved in systemic inflammation, is one of the cytokines that make up theacute phase reaction, stimulates phagocytosis and the production of IL-1 oxidants and thus attenuates all of these procedures by 4.69% [+8.40%] (p-value=0.5749).…”
Section: Discussionmentioning
confidence: 83%
“…11 Banu Güleç et al made the assumption that preoperative Progesterone (PG) treatment might exert protective effects on ovarian I/R injury through its anti-apoptotic and antioxidative properties; since serum and tissue TOS levels, histologic score including vascular congestion, hemorrhage, polymorphonuclear neutrophils, number of apoptotic cells and interstitial edema were significantly lower and tissue TAS levels were higher in treated group (p<0.001). 12 However, the PG pre-treatment decrease was not statistically significant. The present experiment shows that L attenuates the cytokine TNFα levels which is involved in systemic inflammation, is one of the cytokines that make up theacute phase reaction, stimulates phagocytosis and the production of IL-1 oxidants and thus attenuates all of these procedures by 4.69% [+8.40%] (p-value=0.5749).…”
Section: Discussionmentioning
confidence: 83%
“…Marwa M M Refaie et al attributed 15 protective effect of Pioglitazone (PIO), anti-inflammatory, anti-apoptotic and anti-oxidant properties; since it reduced non significantly the induced increased ovarian tissue levels of MDA, NO x , gene expressions of p53, TNFα, iNOS, GSH, HO-1 levels, PPARγ, eNOS gene expressions and the marked ovarian edema, hemorrhage and congestion associated with cell injury in an OIR experiment. Banu Güleç et al made 16 the assumption that preoperative Progesterone (PG) treatment might exert non-significant protective effects on OIR injury through its anti-apoptotic and antioxidative properties; since serum and tissue TOS levels and histologic scores were significantly lower and tissue TAS levels were higher in treated group (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that progesterone alone may protect ovarian function from ischemia-reperfusion injury through its anti-apoptotic and antioxidative properties [123]. More researches are still needed for the role of progesterone in ovarian function.…”
Section: Hormonesmentioning
confidence: 99%